Innovation symbol systems: Multimodal grammars and vocabularies for facilitating mutual innovation knowledge - Stephen Fox; Mariale Moreno; Päivi Vahala (Journal of Innovation & Knowledge (JIK), 2019)
Symbol systems can provide topic-specific languages comprising multimodal grammars and vocabularies. Symbol systems can facilitate mutual knowledge for innovation when people do not already have a common language for effective communication about an innovation. For example, there can be a lack of common language among diverse participants at public co-creation workshops: especially when different participants have different perspectives about the same hyped innovation. In this paper, action research is reported, which involved the development of a multimodal symbol system for facilitating mutual innovation knowledge. Overall, this paper provides two principal contributions to the literature. First, criteria for topic-specific symbol systems are set-out with reference to relevant literature. Second, a practical example of a multimodal symbol system, which meets these criteria, is presented. Together, these contributions introduce new directions for research and practice concerned with facilitating mutual innovation knowledge.
Keywords: O14; O32; O35; 650; Innovation; Mutual knowledge; Symbol systems; Multimodal; Grammar; Vocabulary; Hype; Distributed manufacturing